Side lobe reduction in array antenna by using novel design of EBG - Muhannad Kaml Abdulhameed; M. S. Mohamad Isa; I. M. Ibrahim; Z. Zakaria; Mowafak K. Mohsen; Mothana L. Attiah; Ahmed M. Dinar (Institute of Advanced Engineering and Science, 2020)
A novel design of EBG is used to replace the mushroom like EBG for surrounding the array patch antenna. In order to improve its radiation performances, Electromagnetic band stop for reducing the surface waves effects is presented. The novel design of Triple Side Slotted EBG (TSSEBG) showed an improvement in the antenna efficiency, directivity and gain as compared to the reference antenna without using EBG, due to reduce the surface waves effects which leads to decrease the side lobes. TSSEBG has been introduced by some modifications in conventional mushroom-like EBG structure. Reducing the complexity was achieved by reducing the number of unit cells and vias, in case of used TSSEBG instead of mushroom like EBG. Additionally, the TSSEBG provided triple band gap compared with mushroom like EBG structure which had only one band gap frequency at 6 GHz. The placement of TSSEBG is a flexible structure which provides a good choice in the antenna applications. The simulation results of array patch antenna with and without mushroom like EBG and TSSEBG are arranged in Table 1. This structure has vast applications in satellite communications.